Association between alteration of neutrophil to lymphocyte ratio, platelet to lymphocyte ratio, cancer antigen-125 and surgical outcomes in advanced stage ovarian cancer patient who received neoadjuvant chemotherapy - Ponganun Tuntinarawat; Ratnapat Tangmanomana; Thannaporn Kittisiam (Elsevier, 2024)
Introduction: Optimal resection significantly influences the prognosis of advanced-stage epithelial ovarian cancer (EOC) patients undergoing debulking surgery. In patients who received neoadjuvant chemotherapy (NACT) followed by interval debulking surgery (IDS), the determination of the ideal timing for surgery remains a challenge. Inflammatory markers, including the neutrophil-to-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and CA-125 levels, have been recognized as potential predictive markers. Objective: This study aims to evaluate the predictive value of changes in NLR, PLR, and CA-125 levels following NACT, specifically assessing their impact on surgical outcomes during IDS for advanced-stage EOC. Methods: A retrospective cohort study enrolled advanced-stage EOC patients who underwent NACT followed by IDS at Vajira Hospital in Thailand from January 2009 to June 2023. Data on clinical, surgical, and inflammatory markers were collected, and the predictive value of these markers for suboptimal resection outcomes was assessed. Results: Among the 65 patients, 98.5 % exhibited radiologic responses post-NACT, while 29.2 % experienced suboptimal resections. Univariate analysis did not reveal significant associations between suboptimal resection and NLR changes after the first NACT cycle or alterations in NLR, PLR, and CA-125 levels at the end of NACT. Subsequent analysis suggested that an NLR decrease exceeding 70 % after the first cycle and NACT completion might predict suboptimal resection, yet statistical analyses showed limited prognostic efficacy (AuROC = 0.608 and 0.597). Conclusion: Our study does not support that changes in NLR, PLR, platelet count, and CA-125 levels after NACT reliably predict IDS outcomes. Additional prospective investigations using larger cohorts or a combination of evaluation methods, rather than relying solely on NLR, are recommended.